2013
DOI: 10.1089/jpm.2012.0622
|View full text |Cite
|
Sign up to set email alerts
|

Team Interactions in Specialized Palliative Care Teams: A Qualitative Study

Abstract: Background: Teamwork is a standard of care in palliative care and that is emphasized by leading organizations. When interdisciplinary teams communicate their varied assessments, outcomes may be more than additive due to the synthesis of information. Interprofessionality does not guarantee multidimensionality in health care interventions, however, and that interprofessional teams promote collaboration may be questioned. Aim: The aim was to explore team interaction among team members in specialized palliative ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 22 publications
1
67
0
9
Order By: Relevance
“…This is consistent with research [26] which reported that teamwork with the patient in the palliative care can create a sense of security for the patient and relatives. Our reflection is that teamwork with different professions is necessary as the care of the patient can be highlighted from several perspectives, which contributes to a holistic view.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with research [26] which reported that teamwork with the patient in the palliative care can create a sense of security for the patient and relatives. Our reflection is that teamwork with different professions is necessary as the care of the patient can be highlighted from several perspectives, which contributes to a holistic view.…”
Section: Discussionsupporting
confidence: 90%
“…Healthcare providers (e.g., physicians and nurses) work together to manage patients, and in the area of palliative care, chaplains and social workers are added to the healthcare team for comprehensive care of the patient. Effective interdisciplinary team characteristics are competence, communication, and organization (Klarare et al, 2013), including leadership, clear vision, quality of care, respect for team roles, and individual characteristics (e.g., listening skills, desire to achieve group goals, and interdisciplinary team experience; Nancarrow et al, 2013). Bronstein's (2003) two-part model of optimal interdisciplinary collaboration describes generic components for positive collaboration between social workers and other disciplines.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Interdisciplinary teams are constructed of professionals from many disciplines who bring different perspectives to the team to accomplish the complex task of providing palliative care for a patient and their family. A focus on well-defined roles, leadership type, and development of competence between the professions can increase opportunities for useful collaboration among team members and result in higher quality palliative care (Klarare et al, 2013). …”
Section: Effective Interdisciplinary Palliative Care Teams: Optimal Fmentioning
confidence: 99%
See 2 more Smart Citations